Abutment mechanical complications of a Morse taper connection implant system: A 1‐ to 9‐year retrospective study. (6th July 2022) - Yang, Fan; Ruan, Yan; Liu, Yunqing; Chen, Jianping; Chen, Yunfang; Zhang, Wentao; Ding, Yude; Wang, Linhong
Abstract: Background: The fracture of a Morse tapered abutment connection in an osseointegrated implant is one of the most serious mechanical complications, and it is extremely hard to deal with this complication in clinical practice. Purpose: The aim of this study was to explore the cumulative mechanical complications focus on abutment of a platform switching Morse taper connection implant system after loading, and to perform a retrospective, approximately 1‐ to 9‐year follow‐up study to identify the predisposing factors. Materials and Methods: A total of 495 patients with 945 fitted implants were enrolled in this study with a follow‐up from January 2012 to January 2020. The data of mechanical complications of the abutment, including abutment fracture (AF) and abutment screw loosening (ASL), and possible causative factors were extracted and evaluated statistically. Results: A total of 25 out of 945 (2.65%) cumulative abutment mechanical complications occurred. AF was the most common complication ( n  = 13, 1.38%), followed by ASL ( n  = 12, 1.27%). For AF, gender, type of prosthesis, abutment design, and implant diameter were identified as the causative factors. AF was mostly observed in the single crown of males in molar areas, while ASL was more likely to occur on an angled abutment than on a non‐angled abutment. Moreover, the abutment with the positioning index (/X) had a higher incidence of fracture than the abutment without the positioning index (C/). Conclusions: This study shows that the Morse taper connection is a safe abutment connection. AF occurs more frequently within single crowns in molar area of males, especially with the positioning index (/X), while ASL is more likely to occur in an angled abutment.